ICT interactive whiteboards in an EFL classroom - Piedra Carrión, Verónica; Villavicencio Gordón, Gabriela
Technology has advanced noticeably, nowadays. People even children purchase and use different technological devices all the time. That is why the lack of applied technology in schools, especially in the teaching of English as a Foreign Language (henceforth EFL), is evident. Through the compilation of information gathered by means of surveys, an interview and the reading of literature, we have seen the interest that students have in learning English with Information and Communication Technology (henceforth ICT) tools; specifically, with Interactive Whiteboards (henceforth IWB). Also, issues regarding students? interest are tackled along this project with the purpose of applying this resource appropriately. Additionally, teachers? reluctance to the use of technology is discussed in order to lower facilitators? resistance to introduce technology in their classrooms. Therefore, it is important to remark on its benefits to motivate school principals to invest money in education.